The Translation Techniques of Arabic to English Short Story "The Prophet Muhammad and The Angel Gabriel" - Tristy Kartika Fi'aunillah; Lutfiyah Alindah (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2023)
This article aims to analyze the translation techniques applied in the English translation of an Arabic short story entitled “The Prophet Muhammad and the Angel Gabriel”, as well as to imply the translation ideology in the target language text. The audience of Islamic short story has expanded alongside the growth of the religion’s communities in the world, which is why studying translation techniques in translating Arabic texts into English – the most well-known lingua franca – is substantial. The researcher used Molina and Albir’s translation technique classification. The article reveals that from the 41 techniques found in the target text, the techniques that focus on structure adjustment such as transposition and linguistic compression are the most frequently used, while the techniques that focus on lexical meaning adjustment are significantly fewer. This is also due to the source text that do not contain notably complicated sentences or implicit messages. The structure adjustment techniques make the target text sound more natural and readable implying that the ideology of the translation process is domestication.